Value addition of MXenes as photo-/electrocatalysts in water splitting for sustainable hydrogen production - Pandey, Sudeshana; Oh, Yongsuk; Ghimire, Mukesh; Son, Ji-Won; Lee, Minoh; Jun, Yongseok (Royal Society of Chemistry, 2024)
The energy transition from fossil fuel-based to renewable energy is a global agenda. At present, a major concern in the green hydrogen economy is the demand for clean fuels and non-noble materials to produce hydrogen through water splitting. Researchers are focusing on addressing this concern with the help of the development of appropriate non-noble-based photo-/electrocatalytic materials. A new class of two-dimensional materials, MXenes, have recently shown tremendous potential for water splitting to produce H2via a photoelectrochemical process. The unique properties of emerging 2D MXene materials, such as hydrophilic surface functionalities, higher surface-to-volume ratios, and inherent flexibility, present these materials as appropriate photo-/electrocatalytic materials. Unique value addition and innovative strategies such as the introduction of end-group modification, heterojunctions, and nanostructure engineering have shown the potential of MXene materials as emerging photo-/electrocatalysts for water splitting. When integrated with conventional noble metal catalysts, MXene-based catalysts demonstrated a lower overpotential for hydrogen and oxygen evolution reactions and a remarkable boost in performance for enhanced H2 production rates surpassing those of pristine noble metal-based catalysts. These promote future perspectives for the utilization of chemically synthesized MXenes as alternative photo-/electrocatalysts. Future research direction should focus on MXene synthesis and utilization for surface modification, composite formation, stabilization, and optimization in synthesis methods and post-synthesis treatments. This review highlights the progress in the understanding of fundamental mechanisms and issues associated with water splitting, influencing factors of MXenes, their value addition role, and application strategies for water splitting, including performance, challenges, and outlook of MXene-based photo-/electrocatalysts, in the last five years. Recent advances in the use of MXenes for (photo)electrocatalytic water splitting applications are reviewed.